Interactive storytelling : 10th International Conference on Interactive Digital Storytelling, ICIDS 2017 Funchal, Madeira, Portugal, November 14-17, 2017, Proceedings /: 10th International Conference on Interactive Digital Storytelling, ICIDS 2017 Funchal, Madeira, Portugal, November 14-17, 2017, Proceedings. (2017) - Unknown
No abstract available